An interdisciplinary agent-based multimodal wildfire evacuation model: Critical decisions and life safety. (February 2022) - Siam, M.R.K.; Wang, Haizhong; Lindell, Michael K.; Chen, Chen; Vlahogianni, Eleni I.; Axhausen, Kay
Abstract: This article applies an interdisciplinary agent-based model (ABM) of wildfire evacuation to the devastating 2018 wildfire in Mati, Greece, where the second-deadliest wildfire of the 21st century took place. This model integrates the natural hazard system (wildfire propagation) with the sociotechnical response system comprising social (population response) and engineered (transportation network and shelter location) components. The research objective is to investigate the effects on wildfire casualties of the risk area population's decisions about (1) whether to leave and how long to wait (i.e., departure time); (2) what transportation mode to use (e.g., walking or driving); and (3) how fast to travel. Analysis of several evacuation scenarios shows that the absence of children, multi-modal travel, staged evacuation, and increased shelter capacity lead to a more successful wildfire evacuation. These analyses can help emergency managers improve the effectiveness of their communities' wildfire evacuation plans.